Advantages of Learning Islamic Religious Education With the Quiziz App - Feskariani, Dwi; Innayatullah, Ahmad; Wahidin, Wahidin; Supriadi, Supriadi; Koiruman, Joko Andi; Riyanto, Muklis; Susanto, Edy (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to identify the benefits of the Quizizz application in learning Islamic religious education. This type of research is a literature review. Data was obtained from literature research from several journal articles. The data collection technique used is literature study. The data analysis technique uses qualitative analysis techniques in a deductive way. The results of the study found that the quizizz application in PAI learning provides benefits, namely increasing student involvement, teaching becomes more efficient, giving feedback by teachers becomes faster and increasing students' understanding because it uses a game-like approach so that the material can be remembered by students better. Based on the results of the research, it is recommended for educators to be consistent in improving the quality of learning by using the quizizz application for students.Keywords: Quizizz, Islamic Religious Education, Technology, Education